Arquiteturas Cognitivas construídas no Curso de Administração a distância - Projeto UAB/Banco do Brasil - Giebelen, Jacobus Bernadinus Maria Edwin (2011)
Distance Education brings a big impact on the democratization of higher Education and the University model, as it increases the possibilities of access to higher education. The profile of the people involved in this teaching and learning process is different as they now interact through digital technologies. Another finding regarding Distance Education concerns the cognitive functions, as they are amplified, modified and exteriorized by digital technologies, such as memory, imagination, perception and reasoning. In this perspective, these technologies significantly restructure the consciousness and memory, and consequently, human cognition, and therefore introduce a new order in the traditional ways to understand and act upon the world. Despite the instant growth in the number of courses in Distance Education, reports of failure are accounted of, as a consequence of difficulties in reading and interpreting Learning Management Systems (LMS) or other available learning material. When faced with difficulties in building knowledge and skills, the learner pursues available teaching materials as a possible solution to overcome the encountered challenges. In this sense, this study comprises a theoretical review of concepts and its main objective is to identify the cognitive architecture built in the course material of the Undergraduate Course in Management, Distance Education, of the Pilot Project Open University of Brazil (UAB) / Bank of Brazil , in order to understand how people learn and how knowledge is structured in this context. Thereto, a more refined model of cognitive architecture was elaborated, based on the basic dimensions of cognitive architecture present in the academic literature. The dimensions of this model were identified in the light of theories regarding human cognition and organizational learning in the context of digital technologies, and applied to printed, audiovisual and online course material used in the above mentioned course. This study argues that there are four important dimensions and interconnections of cognitive architectures, and especially highlights the printed media as a support for knowledge building.